Grazing management that regenerates ecosystem function and grazingland livelihoods. Issue 2 (3rd April 2017) - Teague, Richard; Barnes, Matt
Abstract : Adopting a systems view and regenerative philosophy can indicate how to regenerate ecosystem function on commercial-scale agro-ecological landscapes. Adaptive multi-paddock grazing management is an example of an approach for grazinglands. Leading conservation farmers have achieved superior results in ecosystem improvement, productivity, soil carbon and fertility, water-holding capacity and profitability. Their method is to use multiple paddocks per herd with short grazing periods, long recovery periods, and adaptively changing recovery periods, residual biomass, animal numbers and other management elements as conditions change. In contrast, much research on grazing management has not followed adaptive research protocols to account for spatial effects, for sufficient time to produce resource improvement, sound animal production, and socio-economic goals under constantly varying conditions on rangelands. We briefly review what management has achieved best outcomes and show how previous reviews of grazing studies were limited in scope and applicability to larger, more complex landscapes. We argue that future research can provide better understanding of how multi-paddock grazing management can improve socio-ecological resilience in grazing ecosystems, while avoiding unintended consequences of possible management options, by involving realistic scale and context, partnering with innovative land managers on real operations, applying adaptive treatments, and combining field studies with modelling approaches.